2014
DOI: 10.1055/s-0034-1373737
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following Microfracture of Full-Thickness Articular Cartilage Lesions of the Knee in Adolescent Patients

Abstract: The purpose of this study was to document outcomes following microfracture for full-thickness cartilage defects of the knee in adolescents. Our hypothesis was that patients aged 18 years or less would have excellent outcomes and function following microfracture of full-thickness knee articular cartilage defects. This study was approved by the Institutional Review Board. Patients < 19 years old with full-thickness knee articular cartilage defects treated with microfracture between January 1992 and June 2008 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…In der Therapie rein chondraler Defekte unter 2,5 cm 2 Defektfläche gilt die MFx als Verfahren der ersten Wahl [6]. Gerade bei jüngeren Patienten konnten so durchaus auch gute Langzeitergebnisse gezeigt werden [15,16]. Ab einer Defektgröße von 2,5 cm 2 sind jedoch vor allem die mittel-bis langfristigen Ergebnisse der MFx denen der ACT unterlegen [17].…”
Section: Knochenmarkstimulierende Knorpelverfahrenunclassified
“…In der Therapie rein chondraler Defekte unter 2,5 cm 2 Defektfläche gilt die MFx als Verfahren der ersten Wahl [6]. Gerade bei jüngeren Patienten konnten so durchaus auch gute Langzeitergebnisse gezeigt werden [15,16]. Ab einer Defektgröße von 2,5 cm 2 sind jedoch vor allem die mittel-bis langfristigen Ergebnisse der MFx denen der ACT unterlegen [17].…”
Section: Knochenmarkstimulierende Knorpelverfahrenunclassified
“…The authors reported 24 failures (21.82%) in the study population. Steadman et al 6 studied a specific population of 26 patients younger than 19 years (mean defect size, 1.77cm 2 ) treated with MF. In this study, 2-year follow-up was obtained in 22 of 26 patients with an average of 5.8 years.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that in their adolescent population, the three recorded failures were in female patients treated for patellofemoral defects. 6 …”
Section: Discussionmentioning
confidence: 99%
“…58,64-68 Therefore, a subset of young patients with acute, small (<2 cm 2 ), well-shouldered defects in the femoral condyles may be the appropriate candidates for MST treatment. 69-71 However, for most patients, we would not recommend MST alone, especially on the patella, which has worse outcomes than other locations. 72 AMIC may also be considered in these patients as it has shown improved pain and functional outcome scores in patients up to 9 years postoperatively compared to MST alone; however, additional RCTs comparing AMIC to other cartilage therapies are needed.…”
Section: Treatment Algorithmmentioning
confidence: 99%